Understanding and exploiting the nonlinear behavior of tuned liquid dampers (TLDs) for structural vibration control by means of a nonlinear reduced-order model (ROM). (15th January 2022) - Zhang, Zili
Abstract: This paper investigates the nonlinear behavior of tuned liquid dampers (TLDs) and its effects on the vibration control effectiveness of the damper. A nonlinear reduced-order model (ROM) is developed and validated by full-scale experiments, and is used for performing extensive time-domain simulations of both a pure TLD and a structure-TLD system under different excitation conditions. Different nonlinear behaviors of the liquid inside the TLD are predicted by the model, including higher-order harmonic responses, amplitude-dependent responses, jump phenomenon, irregular-shaped hysteretic loops and chaotic motions. It is observed that a shallow-water TLD exhibits hardening spring effect while a deep-water TLD exhibits softening spring effect. In general, a tuned TMD outperforms a tuned TLD, and the performance of the tuned TLD in reducing structural responses is deteriorated with increasing excitation amplitude. However, when both dampers are detuned (tuning ratio larger than the classic value), the shallow-water TLD can outperform the TMD as the excitation amplitude increases due to the hardening effect. This observation has been confirmed from both harmonic excitation and stochastic excitation. On the other hand, a deep-water TLD has the advantage that its performance is less amplitude-dependent and thus more robust. Highlights: A nonlinear reduced-order model (ROM) for TLD is established and validated by experiment. Different nonlinear behaviors of the sloshing liquid are predicted by the ROM. Shallow-water TLD and deep-water TLD exhibit hardening and softening spring effects respectively. Performance of a tuned TLD is worse than a TMD and deteriorates with increasing excitation amplitude. A detuned shallow-water TLD can outperform a detuned TMD by exploiting the hardening effect.